2018
DOI: 10.1016/j.addbeh.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Social media e-cigarette exposure and e-cigarette expectancies and use among young adults

Abstract: A vast majority of U.S. young adults use social media such as Facebook and Instagram daily. Research suggests that young adults are commonly exposed to e-cigarette-related marketing or user-generated content on the social media they use. Currently, however, there is limited empirical evidence as to how social media e-cigarette exposure is associated with e-cigarette use beliefs and behavior. In particular, limited evidence exists to support the proposition that social media e-cigarette exposure is uniquely ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 50 publications
13
103
3
Order By: Relevance
“…Exposure to tobacco promotion on social media among youth aged 11–18 was correlated with a more favourable attitude towards tobacco 25. A study of undergraduate college students between the ages of 18 and 25 years found that greater prevalence of e-cigarette use in an individual’s social network was associated with a more positive ‘smoking experience’ 26. One study found that youth exposure to tobacco depictions on social media better predicts smoking tendency than exposure on television and movies 27.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to tobacco promotion on social media among youth aged 11–18 was correlated with a more favourable attitude towards tobacco 25. A study of undergraduate college students between the ages of 18 and 25 years found that greater prevalence of e-cigarette use in an individual’s social network was associated with a more positive ‘smoking experience’ 26. One study found that youth exposure to tobacco depictions on social media better predicts smoking tendency than exposure on television and movies 27.…”
Section: Discussionmentioning
confidence: 99%
“…Youth and young adults are likely to be affected by their peer groups' perception and prevalence of tobacco use, as well as targeted tobacco marketing [23]. Exposure to e-cigarette marketing may positively affect young adults' perceptions of e-cigarettes [29,30], subsequent use of e-cigarettes [31], as well as perceptions of regular cigarettes [32] and smoking urges [33,34]. Understanding the effect of e-cigarette marketing is particularly important to inform tobacco control, as this understanding may facilitate identifying those who are most vulnerable to the effects of tobacco marketing, and why [6,14].…”
Section: Importance Of Young Adults In Tobacco-related Communicationmentioning
confidence: 99%
“…Given previous research on the effects of e‐cigarette advertising among young adult non‐smokers has shown that positive portrayals of e‐cigarettes result in more favourable attitudes to the devices , maintaining existing regulations on the marketing of e‐cigarettes in Australia and other countries with similarly restrictive regulatory environments (e.g. Canada) should be prioritised in control efforts . In countries with liberal regulations on the marketing of e‐cigarettes (e.g.…”
Section: Discussionmentioning
confidence: 99%